Protein sulfenic acid-mediated anchoring of gold nanoparticles for enhanced CT imaging and radiotherapy of tumors in vivo. Issue 45 (18th November 2020) - Ding, Jianan; Mao, Qiulian; Zhao, Meng; Gao, Yinjia; Wang, Anna; Ye, Shuyue; Wang, Xiaoyan; Xie, Wei; Shi, Haibin
Abstract : Herein, smart protein sulfenic acid-reactive gold nanoparticles were reported as effective radiosensitizers for CT imaging and radiotherapy of tumors. They enable on-site immobilization within tumors resulting in enhanced accumulation and retention. Abstract : Radiotherapy (RT) has become one of the most widely used treatments for malignant tumors in clinics. Developing a novel radiosensitizer for the integration of precise diagnosis and effective radiotherapy against hypoxic tumors is desirable but remains a great challenge. Herein, protein sulfenic acid reactive gold nanoparticles as effective radiosensitizers were for the first time reported for enhanced X-ray computed tomography (CT) imaging and radiotherapy of tumors in vivo . The gold nanoparticles were decorated with biocompatible poly(ethylene glycol), folic acid (FA), and sulfenic acid reactive groups 1, 3-cyclohexanedione (CHD). Such a nanostructure enables on-site immobilization within tumors under oxidative stress through the specific reaction between CHD and endogenous protein sulfenic acids resulting in enhanced accumulation and retention of gold nanoparticles within tumors, which remarkably improves the sensitivity of CT imaging and the radiotherapeutic efficacy of tumors in living mice. This study thus is the first to demonstrate that protein sulfenic acid reactive gold nanoparticles with a tumor anchoring function may serve as effective radiosensitizers for clinical X-ray theranostic application in the future.